A Rabbit Model Study to Determine the Efficacy of a Prototype Corneal Endothelium Protector during Cataract Surgery - Annabel C. Y. Chew; Anita Chan; Monisha E. Nongpiur; Gary Peh; Veluchamy A. Barathi; Nyein C. Lwin; Charles Ong; Shamira Perera (Journal of Ophthalmology)
Purpose. We evaluated the efficacy and safety of a mechanical device, the P-chute, in corneal endothelium preservation during phacoemulsification in a rabbit model. Methods. Twenty-four rabbits were randomly assigned into 2 groups. One eye of each rabbit underwent phacoemulsification that simulated the removal of a dense nucleus, with or without the P-chute. Serial slit-lamp examinations, anterior segment optical coherence tomography (ASOCT) scans, and specular microscopy were performed. Three rabbits from each group were sacrificed on postoperative days (PODs) 1, 5, 7, and 14. Histological analysis of the corneas was performed. Results. There was a trend towards lesser endothelial cell loss for the P-chute group at POD1 (4.9% versus 12.5%, p=0.53), POD5 (10.4% versus 12.2%, p=0.77), and POD7 (10.5% versus 17.2%, p=0.52). There was no significant difference in the corneal thickness (p=>0.05) between the 2 groups. The insertion of the device was challenging. The use of the P-chute only added an extra 15% to the surgical time. Conclusions. There was a trend towards better endothelium preservation with the P-chute even though the results were not statistically significant. We believe that the device could be useful in certain surgical situations. Further work is needed to improve the device insertion.